Development of Instructional Video Media for Special Needs Education to Support Students with Intellectual Disabilities in Independent Learning - Pebisi, Barqun Aknu; Wulansari, Rizky Ema; Rizal, Fahmi; Adri, Muhammad (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop a valid, practical, and effective video-based learning media to support students with intellectual disabilities in learning independently. The research employed a Research and Development (R&D) method using the Four-D model: Define, Design, Develop, and Disseminate. The product was tested with 8 students at SLB Mutiara Budi Lubuk Alung with intellectual disabilities. Data were collected through validity, practicality, and effectiveness evaluations using expert validation sheets, student questionnaires, and performance tests. The data were analyzed quantitatively using percentage scores and categorized based on predetermined criteria. The results showed that the media achieved high validity scores from both media (95%) and content experts (91%), indicating very good validity. The practicality score from student responses was 86%, indicating practicality. Moreover, the effectiveness score based on learning outcomes was 87%, indicating effectiveness. These findings suggest that the developed video-based instructional media is feasible for use and has potential to enhance inclusive science learning by providing accessible, engaging, and self-paced learning experiences.